INCIDENCE AND RISK FACTORS OF MOST PREVALENT CANCERS IN INDIA - BAKHYA SHREE; RADHASARASWATHY (International Journal of Pharma and Bio Sciences, 2015)
The incidence and mortality of any disorder in a country are of much importance in order to realize the impact that it creates among the population. A deadly disease like cancer has to be periodically accounted for its incidence in a population. Cancer which mainly arises due to a mutation at a gene level has found to impart a greater impact in India due to its increasing incidence and mortality in the recent years. This review accounts the incidence of major cancer types in India currently using the primary resources.In this regard the incidence, mortality, risk factors and future perspectives of major types of cancers namely lung cancer, breast, cervical and oral cancers have been discussed. The incidence of the above mentioned types of cancers has been compared with the worldwide incidence data and the importance of cancer genetic counseling has been emphasized.